Interview with Dra. Úrsula Hauser - Ramírez Hernández, Marcela (2019)
Interview with Ph.D. Úrsula Hauser, a long-standing psychoanalyst who has been treating victims of armed conflict. In her work she has converged psychoanalysis and psychodrama in order to build a historical memory from the stories of those who have been affected by war hostilities, to elaborate, thus, another that challenges a hegemonic narrative and procure, at the same time, the formation of an identity process that seeks social justice.